(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Dental professionals are now able to prevent and treat periodontitis with a number of antimicrobial medications because to the identification of microbial specificity in periodontitis over the past three decades. Systemic antibiotics, topical antibiotics, and topical antiseptics are some of them. In order to control periodontal pathogens living in different areas of the mouth from where they may translocate to periodontal sites and to eradicate pathogenic bacteria that infiltrate gingival tissue, systemic antibiotic therapy can be crucial. Metronidazole-amoxicillin (250- 375 mg of each 3 times daily for 8 days) and metronidazole-ciprofloxacin (500 mg of each 2 times daily for 8 days) are two common periodontal combination antibiotic regimens. Microbiological study aids in determining the most effective antibiotic regimen and course of treatment. Topical antiseptics that are important for treating periodontitis include 0.1% sodium hypochlorite solution applied subgingivally by patients using an irrigation device and 10% povidone-iodine solution injected subgingivally by a syringe for five minutes. The current study suggests periodontal therapy using a variety of professionally and privately administered antimicrobial agents (appropriately prescribed systemic antibiotics, povidoneiodine and sodium hypochlorite subgingival irrigants, and chlorhexidine mouthwash). The use of available chemotherapeutics can manage different types of periodontal disease and subgingival colonization of periodontal bacteria in a safe, practical, and inexpensive manner.